Overcoming the Help-Seeker's Dilemma: How Computer-Mediated Systems Encourage Employee Help-Seeking Initiation. Issue 2 (February 2015) - Cleavenger, Dean J.; Munyon, Timothy P.
Helping processes are critical for organizations. Yet, research suggests that there are strong disincentives for employees to seek help from others. Drawing on self-presentation theory, this paper tested how computer-mediated communication may be used to stimulate a help-seeking response from workers. Subjects were placed in an induced-failure work scenario and provided with a computer-mediated channel with which to request help. By experimentally manipulating feedback, anonymity, and interdependence features of the work context, we then measured the length of time before subjects requested help. Eighty three percent of subjects initiated a request for help within the work period, and these help-seeking requests were made more quickly under strong helping norms, high goal interdependence, and high anonymity conditions rather than weak helping norms, low goal interdependence, and low anonymity conditions. The results provide new insights into the design of official communication channels intended to encourage employee help-seeking.